Pengaruh Market Value Added, Basic Earning Power, Return On Investmen Terhadap Return Saham dengan Corporate Social Responsibility sebagai Variabel Moderasi - Septiana Irma Nugraheni; Hari Setiono; Nurdiana Fitri Isnaini (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This study aims to examine the effect of MVA, BEP and ROI on stock returns with CSR as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange. The population used in this study were food and beverage companies listed on the Indonesia Stock Exchange for the period 2021-2023. The sample selection used purposive sampling. Based on purposive sampling, 39 data were obtained from 13 samples that met the criteria with data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id). The data analysis technique used multiple linear regression analysis with SPSS (statistical product and service solutions) tools. The results of this study indicate that MVA has no effect on stock returns, BEP and ROI has an effect on stock returns, CSR is able to moderate MVA and BEP on stock returns, CSR does not moderate ROI on stock returns.